Rediscovery and IUCN threat assessment of Themeda saxicola (Poaceae: Andropogoneae), an endemic grass from the Eastern Ghats, India - Chorghe, Alok R.; Kulloli, R.n. (Phytotaxa, 2022)
Themeda saxicola is an endemic perennial grass rediscovered after laps of 67 years from the Raisili hill (type locality) and Deomali hill, from the Eastern Ghats in the Koraput district of Odisha. The detailed description along with colour photographs of the habitats, habit and floral parts are provided for easy identification of the species. In addition, distribution map and IUCN threat category assessment are also provided.